Backward Design in Pre-Service Teacher Education to Enhance Curriculum Knowledge - Kerimoglu, Esra; Altun, Sertel (UNIV WINDSOR, FAC EDUCATION, 2024)
This action research aimed to enhance the curriculum knowledge of 37 pre-service teachers in early-childhood education through backward design (BD) as an innovative framework. Participants enrolled in an online curriculum development course focusing on curriculum elements and underwent BD-based instruction for five weeks. Multiple data collection tools were employed, including pre- and postachievement tests and curriculum literacy scales, digital learning journals, performance tasks, course observations, and interviews. The results showed a significant improvement in the curriculum knowledge of the pre-service teachers. This was evidenced by a notable increase in curriculum literacy scores, a moderate improvement in achievement test scores, and positive performance task outcomes. These findings highlight the effectiveness of BD-based instruction in enhancing the curriculum knowledge of pre-service teachers. This study provides valuable insights for teacher educators to effectively tailor their instructional approaches. Further research is needed to validate these results and advance instructional practices in pre-service teacher education.
Keywords: CONCEPTUALIZATION; LITERACY; Education & Educational Research